Linking social protection with agriculture and nutrition interventions. Biofortified potato to alleviate anemia in the high Andes of Peru. Project profile - International Potato Center (International Potato Center, 2019)
Many women and children in the high Andes suffer from anemia due to an inadequate diet. This project takes a holistic approach to addressing micronutrient deficiency, boosting food security and health and building women’s empowerment by introducing potatoes rich in iron and zinc as part of an integrated agriculture-nutrition approach.